Odpowiedzi

2009-11-09T17:21:56+01:00
Wykonaj działania:
a) (m+n)(m-2)+(m-n)(m+1)=
=m²-2m+nm-2n+m²+m-nm-n=
=2m²-m-3n

b) (3x-2)(3x-2y+1)-4x(2x-3y+1)=
=9x²-6xy+3x-6x+4y-2-8x²+12xy-4x=
=x²+6xy-x+4y-2
c) 3(m+1)(n-2)+2(n+1)(m-2)=
=3(mn-2m+n-2)+2(nm-2n+m-2)=
=3mn-6m+3n-6+2nm-4n+2m-4=
=5mn-4m-n-10
d) x(x+1)(x+2)-x(x-10)(x-2)=
=x³+2x²+x²+2x-x³+2x²+10x²-20x=
=15x²-18x

mam nadzieje ze sie nie pomylilam:)
2009-11-09T17:24:06+01:00
A) (m+n)(m-2)+(m-n)(m+1)=m²+mn+mn-2n+m²+m-mn-n=2m²+mn-3n+m

b) (3x-2)(3x-2y+1)-4x(2x-3y+1)
=9x²-6xy+3x-6x+4y-2-8x²+12xy-4x
=x²-2xy-7x+4y+12xy

c) 3(m+1)(n-2)+2(n+1)(m-2)
=3(mn-2m+n-2)+2(mn-2n+m-2)
=3mn-6m+3n-5+2mn-4n+2m-4
=5mn-4m-n-9

d) x(x+1)(x+2)-x(x-10)(x-2)
=x(x²+2x+x+2)-x(x²-2x-10x+20)
=x³+2x²+x²+3x-x³+2x²+10x²-20x
=15x²-18x
2009-11-09T17:48:53+01:00
A)
(m+n)(m-2)+(m-n)(m+1)
m²-2m+nm-2n+m²+m-nm-n
2m²-m-3n

b)
(3x-2)(3x-2y+1)-4x(2x-3y+1)
9x²-6xy+3x-6x+4y-2-8x²+12xy-4x
x²+6xy-7x+4y-2

c)
3(m+1)(n-2)+2(n+1)(m-2)
3(mn-2m+n-2)+2(nm-2n+m-2)
3mn-6m+3n-6+2nm-4n+2m-4
5mn-4m-n-10

d)
x(x+1)(x+2)-x(x-10(x-2)
x(x²+2x+x+2)-x(x²-2x-10x-20)
x³+2x²+x²+2x-x³+2x²+10x²+20x
15x²+22x